All at Sea? Maritime Dimensions of Europe's Relations with Africa. Issue 2 (July 2016) - Styan, David
The article examines three dimensions of Europe's maritime relations with Africa: first, the notion that Europe's strategic maritime frontiers are linked to Africa; second, the coherence or 'actorness' of the European Union's (EU) anti-piracy force operating off the Horn of Africa; and third, the relationship between the EU's own military and naval objectives and its wider regional policies in Africa. While the EU adopted a 'Maritime Security Strategy' in 2014, the article notes that, in practice, the EU's strategy at sea has focused on two groups of 'non-state actors': the Africans who are 'pirates'; and the migrants crossing the Mediterranean, who are the object of the EU's Frontex patrols. As such, the initial question examined charts the somewhat fluid notion of the sea as a maritime frontier: where do Europe's strategic interests in terms of its maritime frontiers lie? Is the EU's anti-piracy mission defending them? Is this first-ever maritime mission a more tangible manifestation of EU's common foreign and defence policy than some of the other shorter and smaller military and policing missions in Africa?